2015
DOI: 10.1111/bjd.13829
|View full text |Cite
|
Sign up to set email alerts
|

Mutational status of naevus-associated melanomas

Abstract: Introduction Melanoma origin has always been a debated subject, as well as the role of adjacent melanocytic nevi. Epidemiological and histopathological studies point to melanomas arising either de novo or from a nevus. Methods Sixty-one melanomas found in association with a preexisting nevus were microdissected, after careful selection of cell subpopulations and submitted to Sanger sequencing of the BRAF, NRAS, C-KIT, PPP6C, STK19 and RAC1 genes. Each gene was evaluated twice in all samples by sequencing or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
32
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 79 publications
8
32
1
1
Order By: Relevance
“…This evidence has already been reported [16]. As previously observed [15,[17][18][19], in some samples we have detected co-occurrence of BRAF and NRAS mutations. At the single cell level, mutations in BRAF or NRAS are mutually exclusive [17].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This evidence has already been reported [16]. As previously observed [15,[17][18][19], in some samples we have detected co-occurrence of BRAF and NRAS mutations. At the single cell level, mutations in BRAF or NRAS are mutually exclusive [17].…”
Section: Discussionsupporting
confidence: 90%
“…The frequency of genomic mutations detected in primary tumors correlated with that previously reported [4,15]. Shitara et al showed that laser microdissection does not alter the frequency of BRAF and NRAS mutations [15]. We observed discordances between mutations found in the primary melanoma and the SLN and/or the metastasis in some cases.…”
Section: Discussionsupporting
confidence: 86%
“…Genetic analyses of such histologically contiguous benign nevus-melanoma pairs support the hypothesis that the melanoma cells were derived directly from the nevus cells. 31,6872 Although cases of driver mutation (that is, RAF/RAS ) discordance between paired nevus and melanoma have been reported 70,73 and are interesting mechanistically, these cases appear to be much less common and some may represent coincidental collision lesions between unrelated nevi and melanomas.…”
Section: Relationship Between Nevi and Melanomamentioning
confidence: 99%
“…A major advantage of this highly sensitive and specific immunohistochemistry is to allow an in situ interpretation without requiring the sometimes challenging isolation of naevus, melanoma and nontumour cells. Molecular false negative results are reported in some challenging melanoma samples and could explain some of the discrepant mutational results reported by Shitara et al . Nevertheless, mutation‐specific immunohistochemistry is to date not available for the NRAS Q61K mutant encountered by Shitara et al .…”
mentioning
confidence: 99%
“…recently reported on BRAF and NRAS mutational status in a large series of 61 naevus‐associated melanomas . DNA analyses performed in microdissected naevus and melanoma areas concluded that there were 36 BRAF V600E and 13 NRAS Q61K mutated cases (no other BRAF V600 or NRAS Q61 mutations), with discrepant mutational status between naevi and melanomas in 13 and nine cases, respectively . This high rate of discrepancy requires further consideration.…”
mentioning
confidence: 99%